SURVEY OF VIRAL DISEASES OF PACIFIC WHITE SHRIMP, Litopenaeus vannamei IN INDONESIA - Taukhid Taukhid; Hambali Supriyadi; Isti Koesharyani (Indonesian Aquaculture Journal, 2008)
Penaeid shrimp culture is a major contributor to foreign exchange earning in Indonesia. It has significant impact on economic development of fisheries sector, and leads to be one of prime mover to improve social prosperity. However, shrimp industry particularly black tiger shrimp (Penaeus monodon) has been facing unpredictable situation due to disease problem. The main constrain in correlation to the development of shrimp industry is disease outbreak, especially caused by viral agents. White Spot Syndrome Virus (WSSV) occurred in 1994, causing mass mortality of black tiger shrimp almost in all of the middle and western part of Indonesia. Due to the disease problem, it is estimated that in year 2000, more than 50% of shrimp pond were idle. Pacific white shrimp (Litopenaeus vannamei) or “udang vanamei” was introduced to Indonesia at the end of 1999, and released officially in July, 2001. Response of shrimp farmers to the shrimp rapidly accepted and distributed to many provinces in the country. At the end of 2006, distribution of white shrimp culture was encountered in more than 15 provinces. The seeds are mainly produced from hatcheries located in East Java and Lampung. The information of TSV in Indonesia was reported firstly from East Java at the end of 2002, without a clear history. Since then, survey of TSV distribution was conducted intensively in white shrimp production areas. Beside TSV, population of white shrimp coming to Indonesia also susceptible to White Spot Syndrome Virus (WSSV) and Infectious Hypodermal and Hematopoietic Necrosis Virus (IHHNV) infection. A survey with the aim to know significant viral diseases of white shrimp is needed to set up an alternative strategy to control them. The survey was conducted, firstly in the main production centers of white shrimp; and planned to be continued throughout the country. Samples collection, diagnostic method and data compiled in this study were collected from both active and passive surveillance. Diagnosis of viral diseases infecting white shrimp in this study was focused on TSV, WSSV, and IHHNV agents. Polymerase Chain Reaction (PCR) test has been used as a major diagnostic technique in this study. Progress report of the study showed that TSV spreading limited in controlled areas. The study proved that WSSV and IHHNV have been found in cultured white shrimp. All of the diseases mentioned above tend to be a significant constrain of future white shrimp industry in Indonesia, and special attention should be given in order to protect wide-spread of particular disease from infected to uninfected ones. Also, briefly current status of white shrimp culture development in the country will be discussed in this paper.